2000
DOI: 10.1034/j.1600-0560.2000.027006316.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple infundibulocystic basal cell carcinomas in association with human immunodeficiency virus

Abstract: Infundibulocystic basal cell carcinoma (IBCC) is a relatively recently described variant of basal cell carcinoma that is controversial and not universally accepted. Excluding cases of nevoid basal cell carcinoma syndrome, IBCC usually presents as a small, solitary, superficial lesion on the face of older persons. There have been previous reports of diffusely distributed, multiple similar lesions, but there is disagreement about the diagnosis in these cases. We present a case of a 43-year-old man with multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…106,117 In contrast, other immunosuppressed states have a statistically significant increase in infiltrative-type BCC. 118 More aggressive BCCs have been reported in HIV patients, including metastatic BCC, 119 multiple infundibulocystic BCC, 120 and aggressive morpheaform type in a scar. 121 BCC also has been reported in HIV patients with (likely coincidental) concurrent cancer syndromes: MuirTorre syndrome 122 and Gorlin-Goltz syndrome.…”
Section: Squamous and Basal Cell Carcinomamentioning
confidence: 99%
“…106,117 In contrast, other immunosuppressed states have a statistically significant increase in infiltrative-type BCC. 118 More aggressive BCCs have been reported in HIV patients, including metastatic BCC, 119 multiple infundibulocystic BCC, 120 and aggressive morpheaform type in a scar. 121 BCC also has been reported in HIV patients with (likely coincidental) concurrent cancer syndromes: MuirTorre syndrome 122 and Gorlin-Goltz syndrome.…”
Section: Squamous and Basal Cell Carcinomamentioning
confidence: 99%
“…In the pre-HAART era, several chemotherapeutic agents (bleomycin, vinblastine, vincristine and etoposide) were shown to have activity against KS in case series and small Phase II trials using different combinations and doses of these drugs [84][85][86][87][88]. However, liposomal anthracyclines and taxanes have become established as the backbone of current standard systemic cytotoxic therapy against KS.…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%
“…The identification of patients at risk of CNS relapse remains inconclusive [23]; however, data from immunocompetent individuals suggest that advanced stage, elevated serum LDH and extranodal disease [87] and involvement of specific anatomical sites such as: testes [88,89], paranasal sinuses [90], paraspinal disease, breast [91], renal [84], epidural space [92] and bone [93,94], predict a higher likelihood of CNS relapse.…”
Section: Prevention Of Secondary Cns Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent reports in the literature, however, have shown a wide variation in clinical presentations. Kagen et al 17 reported a 43‐year‐old male with human immunodeficiency virus with multiple flesh‐colored and translucent, dome‐shaped papules diffusely distributed on the face. Kato and Ueno 18 and De Eusebio et al 19 both reported cases in older patients with solitary, flesh‐colored to dark‐red papules enlarging in the head and neck area in which a diagnosis of basal cell carcinoma diagnosis was suspected.…”
Section: Discussionmentioning
confidence: 99%